Effect of Concentration and Frequency of Paclobutrazol Application on Growth and Yield of Shallot - Alia Dewi Palupi; Agus Sulistyono; Nova Triani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Shallot is a horticultural commodity that is always needed for consumption and has high economic value. However, shallot production in East Java has decreased due to the low quality and quantity of shallot seeds. This study aims to determine the effect of concentration and frequency of paclobutrazol application on the growth and yield of shallot. This research was conducted in Sambigede Village, Sumber Pucung Subdistrict, Malang Regency in January-May 2024. The research was arranged using a Split Plot Design with 3 replication. The main plots were paclobutrazol concentrations: 50 ppm, 100 ppm, 150 ppm, and 200 ppm. The subplots were the frequency of paclobutrazol application: 1 time, 2 times, and 3 times. The combination of paclobutrazol concentration of 100 ppm and application frequency of 1 time gave the best results in inhibiting the vegetative phase, increasing tuber dry weight per clump, harvest index, and chlorophyll content. The frequency of paclobutrazol application did not significantly affect the fresh weight of tubers per clump, fresh weight of tubers per plot and dry weight of tubers per plot, but paclobutrazol concentration of 100 ppm affected the fresh weight of tubers per clump. Keywords: Bulbs, Harvest, Paclobutrazol, Shallot, Vegetative.